HARMONI MASJID-GEREJA: Relasi Jamaah Masjid Da’wah Wanita dengan Jemaat GPdI Bukit Zaitun Kendari - Hasan Basri (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2017)
This research focuses on the relation and attitude of Da'wah Wanita Mosque’s community towards GPdI Bukit Zaitun’s community in Kendari. The research data is collected through observation and depth interviews with the community and the mosque’s boards. The results showed that the relationship of Da'wah Wanita Mosque’s community is limited to the church’s boards who live surroundings, for example day-to-day personal relationship at home, while in the church, it is individual’s muammalah. The relationships established in the form of sharing information and material assistance from the church, and the cooperation in the form of a joint commitment to maintain cleanliness, order and beauty of the worship houses. Besides, the mosque’s community attitude tends to be passive tolerance to the church’s community indicated from their acceptance of the church’s existence beside the mosque. In term of communication, they tend to be open-passive, while in willingness of sharing, they are passive-pragmatic, and for cooperation aspect, they are closed-passive. Regarding the existence of the mosque attached to the church, the mosque's community basically understand that it is not in accordance with Islamic teachings and regulations